Trend of Consumer Brand Switching Health Supplement Products during the Covid-19 Pandemic: Triggered by Price Increase and Consumption Value - Dewi Sri Woelandari Pantjolo Giningroem; Novita Wahyu Setyawati; Hadita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Consumer brand switching product or service purchase is very important to know, because when consumers are satisfied and their wants and needs are met then what ever brand they will be used them. This study aims to analyze the factors that can prevent consumers brand switching and assess price increases and consumption behavior in directing consumers to buy healthy supplement product vitamin C1000+Zinc Sido Muncul drinks and to examine which factor are more dominant influencing consumers to pull off brand swithing. Sample in this study are people of the City of Bekasi. Sample respondents was selected using purposive sampling technique and obtained a sample of 86 respondents. The data analysis technique in this study used the regression method with SPSS software version 23 for data analysis. The results shows that the price increase factor was more dominant influence consumers to pull off brand switching compared consumption behavior factor.